ANALYSIS OF THE PERSPECTIVES OF THE TRANSATLANTIC PARTNERSHIP EXISTENCE - L. Chuvakhina (Вестник университета)
The article deal with the problem of the formation of the Transatlantic trade and investment partnership with the participation of the USA and the European Union. The main objectives of the partnership are: increasing the volume of the mutual trade and investment by reducing customs barriers, harmonizing standards, unifying the legal foundations of trade and investment activities. Due to serious disagreements in the issues of trade in agri-food products, the negotiation process dragged on. Certain hopes for the resuscitation of the multilateral negotiation process due to the apparent unwillingness of the countries of the continental Europe to switch to bilateral cooperation with the United States did not come true. It is concluded that the European Union leadership raised prematurely the issue of resuming negotiations with the administration of D. Trump.